A qualitative follow‐up study of diabetes patients' appraisal of an integrated diabetes service in primary care. (26th October 2016) - Burridge, Letitia H.; Foster, Michele M.; Donald, Maria; Zhang, Jianzhen; Russell, Anthony W.; Jackson, Claire L.
Abstract: As the prevalence of type 2 diabetes continues to escalate, health system reform is seeking better patient outcomes through new models of care that aim to provide the most appropriate care when needed. Patients' experiences of service innovations can shed light on the successes and challenges of implementing change. This paper explores patients' views of a new model of integrated care for patients with type 2 diabetes. A mixed‐methods, randomised control trial evaluated a beacon clinic model of care for complex type 2 diabetes led by specialist general practitioners (GPs) in primary care settings in Brisbane, Australia. In this qualitative sub‐study conducted between May 2014 and January 2015, 25 consenting participants were re‐interviewed after 12 months using semi‐structured questions, to explore their experiences of the new model of care. Interview transcripts were analysed thematically. In the first theme, Organised for patient‐centred care, patients appraised the structural elements of the clinic. For most, it was an enabling experience which included convenience, flexibility and prompt communication back to the referring GPs. The preferences of a minority were partly realised, as they tried to understand the clinical purpose in comparison with traditional care. The second theme, Positioned as partners in care, revealed the pivotal role of patient–clinician relationships in patients' engagement with advice and self‐care. Most found clinicians' collaborative approach engaging and motivating. A small minority with contextual concerns were disappointed with the focus on diabetes and struggled to engage fully with the model. Most participants valued this model of care, which reflects a capacity to manage the variable and complex needs of most patients referred for care. However, multi‐level strategies are also needed to enhance patients' engagement with care and the sustainability of integrated diabetes care.